Penerapan Program Ecobric untuk Meningkatkan Kesadaran Masyarakat terhadap Kebersihan di Desa Sihite II - Alfia Utami; Siti Khoirotun Nisa; Amanah Putri Fadillah; Alfin Alfarihin; Rholand Muary (Universitas 45 Surabaya, 2025)
Plastic waste remains a significant environmental challenge, particularly in rural areas with limited or nonexistent waste management infrastructure. This study investigates the implementation of the Ecobrick program in Sihite II Village and evaluates its impact on raising environmental awareness and promoting active community participation in sustainable waste management practices. Employing a qualitative descriptive approach through direct observation and literature review, the findings indicate that prior to the program, environmental hygiene was poor, with plastic waste scattered across the village. Community outreach activities effectively improved residents’ understanding of proper waste handling. Furthermore, the hands-on process of creating Ecobricks provided new skills and shifted local perceptions, demonstrating that waste materials can be transformed into valuable resources. A tangible outcome of the program was the construction of a village signboard made from Ecobricks, symbolizing both environmental consciousness and local identity. Overall, the program contributed to a reduction in plastic waste and fostered a culture of sustainable environmental stewardship within the community.